CSC118: Fundamentals of Algorithm Development / College of Computing, Informatics and Media - UiTM, College of Computing, Informatics and Media (Universiti Teknologi MARA (UiTM), 2023)
This course will focus on algorithm development in problem solving. It will also introduce the students to the techniques of problem solving using modular approach. Students are expected to analyze, develop the solution to problems given. This course will also provide the overview of the computer system and introduction to array concept.